2020
DOI: 10.1089/neu.2018.5959
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multi-Dimensional Analysis of Rodent Gait Reveals the Compensation Strategies Used during Spontaneous Recovery from Spinal Cord and Traumatic Brain Injury

Abstract: As rodent locomotion becomes a more popular behavioral assay, proper rodent gait analysis becomes more and more important. Gait measures, such as stride length, cycle time, and duty factor, are not independent of one another, making statistical comparisons between groups a tricky endeavor. Instead of identifying the mathematical relationships between a group of locomotor measures, we simply tracked the steps of rodents in x,y,t space. By plotting with respect to the reference limb, we are able to quantify loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The keywords used in the search process were CatWalk, rodents, mouse, mice, and the diseases of interest for our study. The majority of the studies (86%) were published between 2017 and 2022 ( Baiguera et al, 2012 ; Bernardes et al, 2017 ; Caballero-Garrido et al, 2017 ; Carboni et al, 2017 ; Chen et al, 2017 , 2019 , 2020 ; Cline et al, 2017 ; Fujimaki et al, 2017 ; Hayashi et al, 2017 ; Hsieh et al, 2017 ; Matyas et al, 2017 ; Mountney et al, 2017 ; Ni et al, 2017 ; Pöttker et al, 2017 ; Rocca et al, 2017 ; Roth et al, 2017 ; Schönfeld et al, 2017 ; Crowley et al, 2018 , 2019 ; Du et al, 2018a , b ; Frahm et al, 2018 ; Fröhlich et al, 2018 ; Liu et al, 2018 , 2019 ; Lu et al, 2018 ; Mozafari et al, 2018 ; Noristani et al, 2018 ; Okuwa et al, 2018 ; Sowa et al, 2018 ; Su et al, 2018 ; Timotius et al, 2018b , 2021 ; Truong et al, 2018 ; Zhu et al, 2018 ; Cross et al, 2019 ; Guy et al, 2019 ; Kolosowska et al, 2019 ; Leite et al, 2019 ; Ma et al, 2019 ; Minakaki et al, 2019 ; Minarelli et al, 2019 ; Miterko et al, 2019 ; Pacheco et al, 2019 ; Thau-Zuchman et al, 2019 ; Bengoa-Vergniory et al, 2020 ; Campos-Pires et al, 2020 ; Chung et al, 2020 ; Goldshmit et al, 2020 ; Goncalves et al, 2020 ; Heinzel et al, 2020a ; Henry et al, 2020 ; Lin et al, 2020 , 2022 ; Murphy et al, 2020 ; Namdar et al, 2020 ; ...…”
Section: Methodsmentioning
confidence: 99%
“…The keywords used in the search process were CatWalk, rodents, mouse, mice, and the diseases of interest for our study. The majority of the studies (86%) were published between 2017 and 2022 ( Baiguera et al, 2012 ; Bernardes et al, 2017 ; Caballero-Garrido et al, 2017 ; Carboni et al, 2017 ; Chen et al, 2017 , 2019 , 2020 ; Cline et al, 2017 ; Fujimaki et al, 2017 ; Hayashi et al, 2017 ; Hsieh et al, 2017 ; Matyas et al, 2017 ; Mountney et al, 2017 ; Ni et al, 2017 ; Pöttker et al, 2017 ; Rocca et al, 2017 ; Roth et al, 2017 ; Schönfeld et al, 2017 ; Crowley et al, 2018 , 2019 ; Du et al, 2018a , b ; Frahm et al, 2018 ; Fröhlich et al, 2018 ; Liu et al, 2018 , 2019 ; Lu et al, 2018 ; Mozafari et al, 2018 ; Noristani et al, 2018 ; Okuwa et al, 2018 ; Sowa et al, 2018 ; Su et al, 2018 ; Timotius et al, 2018b , 2021 ; Truong et al, 2018 ; Zhu et al, 2018 ; Cross et al, 2019 ; Guy et al, 2019 ; Kolosowska et al, 2019 ; Leite et al, 2019 ; Ma et al, 2019 ; Minakaki et al, 2019 ; Minarelli et al, 2019 ; Miterko et al, 2019 ; Pacheco et al, 2019 ; Thau-Zuchman et al, 2019 ; Bengoa-Vergniory et al, 2020 ; Campos-Pires et al, 2020 ; Chung et al, 2020 ; Goldshmit et al, 2020 ; Goncalves et al, 2020 ; Heinzel et al, 2020a ; Henry et al, 2020 ; Lin et al, 2020 , 2022 ; Murphy et al, 2020 ; Namdar et al, 2020 ; ...…”
Section: Methodsmentioning
confidence: 99%
“…Sham injury consisted of anesthesia and the midline incision, with no craniotomy or impact. Wound clips were removed 10–14 days post-surgery [ 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the tremendous differences in brain structure, these TBI model rodents exhibit relatively low physiological and pathological similarities with clinical features of human TBI 16 . In addition, the evaluation methods for effective TBI repair in many studies are singular and unobjective 17 . From both anatomical and functional perspectives, a limited number of studies have objectively revealed locomotory improvements of hemiplegic limbs after TBI repair 16 .…”
Section: Introductionmentioning
confidence: 99%